The Fiqh Views On The Impacts Of Pornography And Pornoaction On Physical And Mental Health - Meirison .; M. Adil Syafi'i; Mayang Putri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Pornography and porno-action occur because of modernization and globalization, impacting social life. Islam as an early doctrine serves to solve problems, so many verses of the Qur'an and hadith regulate clothing communication between men and women. Pornography and pornography in the perspective of Islamic law are prohibited; this is based on several verses in the Qur'an and several hadiths of the Prophet Muhammad, which expressly prohibit them. This is inseparable from the development of human culture. By conducting a literature review and qualitative approach, it was found that pornography damages religious morals and human morals and spreads to the human body itself, which will disrupt the human nervous coordination system controlled by the brain. This is difficult to stop because pornography is part of a commodity that generates billions of rupiahs. Sometimes pornography has also developed foreign exchange for countries that produce and trade it officially. Pornography can not only damage children's minds and mentality but can also be fatal for adult human brains. Keywords: Influence, pornography, health, fiqh